TRANSFORMASI KOMUNIKASI EDUKATIF DI ERA DIGITAL: ANALISIS KAJIAN PUSTAKA TENTANG PERAN INTERAKSI, TEKNOLOGI, DAN LITERASI DIGITAL DALAM MENINGKATKAN EFEKTIVITAS PROSES PEMBELAJARAN ABAD KE-21 - Ignatius Septo Pramesworo; Rosdiana Mata; Rosijanih Arbie (CV. Lafadz Jaya, 2026)
The transformation of educational communication in the digital age has become a crucial issue in the context of 21st-century learning, along with changes in interaction patterns, the role of technology, and the need for digital literacy. This article systematically examines the role of interaction, technology, and digital literacy in improving the effectiveness of the learning process through a literature review approach. The results of the study show that information and communication technology has changed educational communication from a one-way model to a more dialogical, participatory, and digital platform-based interaction. On the other hand, digital literacy serves as a catalyst that strengthens students' critical thinking, collaboration, and communication skills, while ensuring the critical and responsible use of technology. Thus, the synergy between interaction, technology, and digital literacy is the main foundation for effective and relevant educational communication in 21st-century learning.